Designing and development of polyvinylpyrrolidone-tungsten trioxide (PVP-WO3) nanocomposite conducting film for highly sensitive, stable, and room temperature humidity sensing. (1st November 2021) - Khan, Hizb Ullah; Tariq, Muhammad; Shah, Mutabar; Ullah, Sajid; Ahsan, Abdul Razaq; Rahim, Abdur; Iqbal, Jibran; Pasricha, Renu; Ismail, Issam
Abstract: In the present research work, highly sensitive, stable, capacitive type humidity sensor based on polyvinylpyrrolidone and tungsten trioxide (PVP/WO3 ) nanocomposite was successfully developed. The sensing materials were prepared by using simple ultrasonication method and were characterized systematically through Fourier transform infrared spectroscopy, X-ray diffraction, high resolution transmission electron microscopy. Drop casting technique was used to develop sensing device using interdigitated copper electrode. Humidity sensing properties of PVP/WO3 nanocomposite sensors were investigated thoroughly and compared with pure PVP and WO3 sensors. It was observed that the humidity sensor with 20 wt% WO3 content showed high response of 44.73 nF/%RH, short response (10 s) and recovery time (15 s) as compared to pristine PVP and WO3 sensor. Low hysteresis value of 1.3 % was observed for PVP/WO3 20 wt% nanocomposite sensor along with excellent stability and repeatability.